Presuppositions Used by Yang Jong Hoon in Law School - Alessandra Virginia Manurung; Aylanda Hidayati Dwi Nugroho (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
This study investigates the presuppositions in Yang Jong Hoon’s utterances in the series "Law School". This study aims to understand how presuppositions are used by lawyers and prosecutors. The theories used are by Yule (1996, 2020). The findings reveal the similarities and differences in the use of presuppositions when Yang Jong Hoon was a prosecutor and a lawyer. A similarity between both roles is that factive presupposition only occurred once as these professions require credibility. The most prominent types of presupposition, however, show differences. In Yang Jong Hoon’s utterances as a prosecutor, existential presupposition appears most frequently to successfully charge the defendant as guilty, often done by presenting proof. In contrast, in Yang Jong Hoon’s utterances as a lawyer, lexical presupposition appears most frequently to recount the situation and thus use change-of-state verbs. The study concludes that an understanding and strategic use of presuppositions are essential in legal debates.